Quality evaluation of data management plans at a research university. (March 2017) - Van Loon, James E.; Akers, Katherine G.; Hudson, Cole; Sarkozy, Alexandra
With the emergence of the National Science Foundation requirement for data management plans, academic librarians have increasingly aided researchers in developing these plans and disseminating research data. To determine the overall quality of data management plans at Wayne State University, the Library System's Research Data Services team evaluated the content of 119 plans from National Science Foundation grant proposals submitted between 2012 and 2014. The results of our content analysis indicate that, while most researchers understand the need to share data, many data management plans fail to adequately describe the data generated by the project, how data will be managed during the project, or how data will be preserved and shared after the completion of the project. Our results also show that data management plan deficiencies vary across academic units, suggesting the need for differentiated outreach services to improve the strength of data management plans in future National Science Foundation grant proposals.